Genetic variation and genotype X environment interaction for yield and other agronomic traits in cassava in Nigeria - Egesi, Chiedozie N.; Ilona, Paul; Ogbe, F.O.; Akoroda, M.O.; Dixon, A. (Wiley, 2007)
The identification of superior genotypes and mega-environments on the basis of multiple traits is a key objective of multi-environment trials in cassava (Manihot esculenta Crantz). The objective of this study was to examine the genetic variation and genotype 3 environment interaction (GEI) effects for fresh root yield, six other agronomic traits, and severity ratings for cassava mosaic disease (CMD) and cassava green mite (CGM) in 40 genotypes of cassava. Experiments were conducted using a randomized complete-block design with four replications for 2 yr in three representative agro-ecological zones in Nigeria. Site regression (SREG) analysis revealed that GEI was a major source of fresh root yield variation and the different testing sites discriminated among the genotypes. Genotypes TMS 980581, TMS 974763, TMS 980002, TMS 993073, and M980068 were highest yielding at Otobi and Umudike, whereas TMS 980510, TMS 974779, and TMS 92B00068 yielded the most at Ishiagu. TMS 982226, TMS 920325, and M980028 had the poorest performance across all locations. Genotypes with the highest yield showed the lowest CMD scores, whereas very tall (well above 2 m) plants had low harvest index on the basis of multiple trait analysis. We identified optimally adapted genotypes for commercial cassava production in different areas in Nigeria.